The Study Deformation Of Bore Pile Foundation Caused by Horizontal Load In Soft Clay - Jehlaeh, Fadel; Darjanto, Helmy; Sutowijoyo, Hendro (International Journal of Engineering, Science and Information Technology, 2021)
A sturdy of building must be contain with a strong foundation, which is able to withstand the burden on it;Â  channel the load into the ground and be able to withstand external forces such as earthquakes. In this study discussed the deformation of the bore pile foundation due to horizontal load on the soil slope by using the Lpile application.TheÂ  aim is to know the displacement of foundation motion due to horizontal loads using the Lpile application, Lateral bearing capacity analysis which is important aspect in the design of the foundation to anticipate the failure of the pile foundation. One method is the p-y curve, It is a development of the Beam method in the Winkler Foundation.